Transition-metal-free intramolecular Friedel–Crafts reaction by alkene activation: A method for the synthesis of some novel xanthene derivatives - Yıldız, Tülay; Baştaş, İrem; Başpınar Küçük, Hatice (Beilstein Journal of Organic Chemistry, 2021)
In this work, new derivatives (substituted 9-methyl-9-arylxanthenes) of xanthene compounds (5a–l) of possible biological significance were synthesized by developing a new synthesis method. In order to obtain xanthene derivatives, the original alkene compounds to be used as the starting materials were synthesized in four steps using appropriate reactions. A cyclization reaction by intramolecular Friedel–Crafts alkylation was carried out in order to synthesize the desired xanthene derivatives using the alkenes as starting compounds. The intramolecular Friedel–Crafts reaction was catalyzed by trifluoroacetic acid (TFA) and provided some novel substituted 9-methyl-9-arylxanthenes with good yields at room temperature within 6–24 hours. As a result, an alkene compound was used for activation with TFA in the synthesis of xanthene through intramolecular Friedel–Crafts alkylation for the first time.
Keywords: alkene activation; intramolecular Friedel–Crafts alkylation; trifluoroacetic acid; xanthene